VD_FINDINFO HC / 2020 / 761 vom 13. November 2020 - VD Tribunal cantonal (2020)
REJET DE LA DEMANDE, COMPÉTENCE, RÉSIDENCE HABITUELLE, PÉRIL EN LA DEMEURE | 10 LDIP, 85 al. 1 LDIP, 11 CLaH 96, 5 CLaH 96